Impaired maturation of resting-state connectivity in anorexia nervosa from adolescence to adulthood: differential mechanisms of consummatory vs. anticipatory responses through a symptom provocation paradigm - Mendez-Torrijos, Andrea; Selvakumar, Mageshwar; Kreitz, Silke; Roesch, Julie; Dörfler, Arnd; Paslakis, Georgios; Krehbiel, Johannes; Steins-Löber, Sabine; Kratz, Oliver; Horndasch, Stefanie; Hess, Andreas (Frontiers in Behavioral Neuroscience, 2024)
This fMRI study examined resting-state (RS) connectivity in adolescent and adult patients with anorexia nervosa (AN) using symptom-provocation paradigms. Differential food reward mechanisms were investigated through separate assessments of responses to food images and low/high caloric food consumption.Thirteen young (≤ 21 years), seventeen adult (> 21 years) patients with AN and age-matched controls underwent 2 stimulus-driven fMRI sessions involving RS scans before and after the presentation of food-related stimuli and food consumption. Graph-theory and machine-learning were used for analyzing fMRI and clinical data.Healthy controls showed widespread developmental changes, while young AN participants exhibited cerebellum differences for high-calorie food. Young AN displayed increased connectivity during potato-chips consumption compared to zucchini, with no differences in adult AN. Multiparametric machine-learning accurately distinguished young AN from healthy controls based on RS connectivity following food visual stimulation ("anticipatory") and consumption ("consummatory").This study highlights differential food reward mechanisms and little developmental changes in RS connectivity from youth to adulthood in AN compared to healthy controls. Young AN individuals demonstrated heightened reactivity to high-caloric foods, while adults showed decreased responsiveness, potentially due to desensitization. These findings shed light on aberrant eating behaviors in AN and contribute to our understanding of the disease's chronicity.